مفهوم المواطنة في المناهج والمقررات التعليمية في مرحلة التعليم الثانوي بالجزائر - بوديار,عبد الحميد; بالطاهر,النوي (University of Eloued جامعة الوادي, 2024)
الملخص : يتناول هذا المقال مفهوم المواطنة كما يتم تجسيده في المناهج والمقررات التعليمية في المرحلة الثانوية بالجزائر, يهدف البحث إلى تحليل كيفية تضمين هذا المفهوم في المناهج الدراسية المختلفة، مع التركيز على مدى توافقها مع الأهداف التربوية لتعزيز قيم المواطنة, يستعرض المقال التمثلات المتنوعة للمواطنة التي يتبناها المعلمون والتلاميذ، ويستكشف التحديات التي تواجه تنفيذ هذه القيم في الحياة اليومية للمتعلمين, يتضمن البحث أيضًا تقييمًا لتأثير المناهج التعليمية في تشكيل وعي التلاميذ بالمواطنة، ويسعى لتقديم توصيات لتحسين فعالية هذه المناهج في تحقيق الأهداف المنشودة. من خلال هذه الدراسة، يتم تسليط الضوء على أهمية التعليم في بناء مجتمع مدني واعٍ ومشارك. Abstract : This article addresses the concept of citizenship as embodied in the curricula and educational programs of secondary education in Algeria. The research aims to analyze how this concept is integrated into various school subjects, focusing on their alignment with educational goals for promoting citizenship values, The article reviews the diverse representations of citizenship adopted by teachers and students and explores the challenges faced in implementing these values in the daily lives of learners, It also includes an assessment of the impact of educational curricula on shaping students' awareness of citizenship and seeks to provide recommendations for enhancing the effectiveness of these curricula in achieving the desired objectives. Through this study, the importance of education in building a conscious and participatory civil society is highlighted.
المضامين والتمثلات
Keywords: مواطنة; مناهج تعليمية; قيم المواطنة; Citizenship; Educational Curricula; Citizenship Values; Secondary Education